Sail the Summer Sky (an Ode to Prairie Birds) - Annie Wilson (Symphony in the Flint Hills, 2011)
An ode to the great birds of Kansas describing their characteristics and unique personalities that make them special.
Keywords: summer; birds; prairie; poem; poetry; Prairie chicken; red-tailed hawk; Upland Plover; Great Blue Heron; Western Meadowlark; Killdeer